Wild chimpanzees remember and revisit concealed, underground army ant nest locations throughout multiple years - Andreu Sánchez-Megías; Carlota F. Galán-Plana; Nadia Mirghani; Laia Dotras; Jordi Galbany; Manuel Llana; Adrián Arroyo; Justinn Renelies-Hamilton; R. Adriana Hernandez-Aguilar (Communications Biology)
Abstract Chimpanzees use spatiotemporal cognition for fruit foraging by remembering tree locations and fruiting seasons. However, the spatiotemporal cognition behind exploiting other foods has rarely been studied. Here, we investigate whether chimpanzees use memory to exploit concealed, underground army ant nests. We analyse 679 chimpanzee visits to four nests recorded during five years (2018–2022) using camera traps in a savanna habitat. We explore if chimpanzees intentionally revisit nests, study how they detect ants, and assess ant availability and chimpanzee ant consumption. Nests are concealed, scarce, and intermittently reoccupied, yet chimpanzees eat ants frequently. We find that out of 34 identified chimpanzees who visit the nests, 23 revisit at least one. Chimpanzees visit nest sites significantly more often than similar sites without nests. Individuals revisit significantly sooner and inspect significantly longer nests where they have more recently encountered ants. The apes use sight, smell, taste, touch, and probing tools, to detect ants inside nests. We provide the first evidence suggesting that chimpanzees use spatial and episodic-like memory to exploit concealed social insects throughout multiple years. Our results expand our understanding of the cognitive strategies behind chimpanzee insectivory, suggesting it may have played an important role in the evolution of primate spatiotemporal cognition.